Therapeutic hypothermia for neonates with hypoxic ischemic encephalopathy - Ming-Chou Chiang; Yuh-Jyh Jong; Chyi-Her Lin (Elsevier, 2017)
Therapeutic hypothermia (TH) is a recommended regimen for newborn infants who are at or near term with evolving moderate-to-severe hypoxic ischemic encephalopathy (HIE). The Task Force of the Taiwan Child Neurology Society and the Taiwan Society of Neonatology held a joint meeting in 2015 to establish recommendations for using TH on newborn patients with HIE. Based on current evidence and experts' experiences, this review article summarizes the key points and recommendations regarding TH for newborns with HIE, including: (1) selection criteria for TH; (2) choices of method and equipment for TH; (3) TH prior to and during transport; (4) methods for temperature maintenance, monitoring, and rewarming; (5) systemic care of patients during TH, including the care of respiratory and cardiovascular systems, management of fluids, electrolytes, and nutrition, as well as sedation and drug metabolism; (6) monitoring and management of seizures; (7) neuroimaging, prognostic factors, and outcomes; and (8) adjuvant therapy for TH. Key Words: hypoxic ischemic encephalopathy, neonate, patient care, perinatal asphyxia, therapeutic hypothermia